Multimodality of School Brochure - Isti Ramona Lubis; Anna Riana Suryani Tambunan; Rahmad Husein (STIBA IEC JAKARTA, 2024)
This study aims to analyse the verbal and visual elements in a school brochure, namely the brochure of Yayasan Perguruan Sultan Iskandar Muda, North Sumatra. The brochure of this school was downloaded from the school's Instagram regard that's chosen aimlessly. The last result of the research reveals that the brochure has all general structure which is lead, view or display, emblem (verbal), announcement, enhancer, emblem (visual), and call- and- visit information. The finding of academy or school brochure completely supports all the theories of this research. The elements of this visual and verbal support each other and cohere to convey a communication to the anthology. The communication conducted to readers come more conclusive, and it attract their interest to school as the source of formal education.